SRC voting system with face authentication - Piam, Emrul Hasan; Mahmud, Ashik; Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Wani, Sharyar; Abubakar, Adamu; Olowolayemo, Akeem Koye (IIUM, 2021)
The aim of this development is to initiate an online voting system, which is secure, has a user - friendly interface and involves functions such as holding elections, taking surveys and facial authentication. In-person voting has many downsides which includes absence of voters due to their busy schedule and alteration of the election results. The online voting system can be accessed by the voters easily from their device and the voting records in the system cannot be altered which will give a fair result. To develop the online voting system, Laravel was used, which is a PHP framework. For face authentication, python deep learning was used. The developed system can be used to hold elections properly, take surveys, make announcements, and make use of face authentication for identification before a ballot is cast. As a result, conducting online elections has more security layers than a normal election which gives a fair outcome and it is less time consuming for the students when tested with 1000 dummy data.